Scott-Conner & Dawson essential operative techniques and anatomy - Scott-Conner, Carol E. H. (Wolters Kluwer/Lippincott Williams & Wilkins Health, 2014)
"To better reflect its new and expanded content, the name of the 4th edition of Operative Anatomy has been changed to Essential Operative Techniques and Anatomy. In this latest edition, the text's focus on clinically relevant surgical anatomy will still remain, but it is now organized by anatomical regions rather than by procedures. Then to further ensure its relevance as a valuable reference tool, the number of chapters has been expanded to 134 and the color art program has also been increased significantly. Written for surgical residents, this book provides an up-to-date, easy-to-use reference for nearly all procedures with which they will face in their residency. Providing a blend of both surgical anatomy and a surgical atlas, this edition covers all Essential Common procedures from the SCORE curriculum as well as many of the Essential Uncommon procedures such as urgent operations seen in general surgery practice. FEATURES: Covers all Essential Common procedures in SCORE curriculum, Significantly expanded chapter on thoracoscopic surgery of the esophagus, Significantly expanded chapter on laparoscopic colon resection, New chapters on cutaneous infections, I&D, excision, STSG, ligation, stripping, saphenous vein, loop ileostomy/closure, operations for small bowel obstruction (including laparoscopic), and pediatric umbilical hernia repair"--Provided by publisher.